(untitled) (Journal of Forestry, 2025)
The Mediterranean region is characterized by diverse landscapes and unique climatic conditions, making this region of crucial importance in the context of wildfires. Türkiye is one of the largest countries in the Mediterranean region with remarkable ecological richness, characterized by diverse land covers encompassing a variety of ecosystems and habitats. Fires play a crucial role in shaping ecosystems in fire prone areas in the country. Understanding the relationship between vegetation composition, climatic factors and historical fire patterns is thus crucial for effective fire management and conservation efforts in the Eastern Mediterranean and the world in general. This study reports and discusses fire dynamics in Türkiye spanning from 2001 to 2020 across diverse land cover classes, employing both the ESA FireCCI51 burned area product and ground-based fire data. This study aims to provide insights into the complex relationship between wildfire activities by examining the interactions and long-term climate variables, vapor pressure deficit (VPD) and the Angström index. The analysis of FireCCI51 data revealed different spatial patterns of wildfire occurrence in different landscapes of the study area. Fires were mainly concentrated in needle-leaved and shrubland landscapes in the west and south, while broad-leaved, herbaceous, and agricultural fires were prevalent in various parts of Türkiye. Despite legal restrictions, stubble burning remains a common practice, contributing to fire occurrences, especially during dry and hot periods after harvest. Long-term climate trends, particularly increasing VPD and decreasing rainfall, significantly impact wildfire dynamics in the study area. High VPD values correlate well with increased fire activity, indicating its role in fuel moisture and burned area. The increasing trend in VPD and decreasing trend in the Angström index underscores the landscape’s increasing susceptibility to wildfires, suggesting a potential impact of climate change on burned area.